The impact of televised tobacco control advertising content on campaign recall: evidence from the International Tobacco Control (ITC) United Kingdom Survey - Richardson, Sol; McNeill, Ann; Langley, Tessa; Sims, Michelle; Gilmore, Anna B.; Szatkowski, Lisa; Heath, Robert; Fong, Geoffrey T.; Lewis, Sarah (BioMed Central, 2014)
BACKGROUND: Although there is some evidence to support an association between exposure to televised tobacco control campaigns and recall among youth, little research has been conducted among adults. In addition, no previous work has directly compared the impact of different types of emotive campaign content. The present study examined the impact of increased exposure to tobacco control advertising with different types of emotive content on rates and durations of self-reported recall.